2012
DOI: 10.1186/1687-9856-2012-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of response to 2-years’ growth hormone treatment in children with isolated growth hormone deficiency, born small for gestational age, idiopathic short stature, or multiple pituitary hormone deficiency: combined results from two large observational studies

Abstract: BackgroundFew studies have compared the response to growth hormone (GH) treatment between indications such as isolated growth hormone deficiency (IGHD), born small for gestational age (SGA), idiopathic short stature (ISS), and multiple pituitary hormone deficiency (MPHD). The aim of this analysis of data, collected from two large ongoing observational outcome studies, was to evaluate growth and insulin-like growth factor-I (IGF-I) response data for children of short stature with IGHD, MPHD, SGA, or ISS followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 30 publications
(43 reference statements)
1
41
1
2
Order By: Relevance
“…Despite such discrepancies, it is worth remarking that GH levels were very similar among the individual diagnostic groups and across the 3 regions ( Table 2 ). While the height pattern in prepubertal males and females in this study was comparable to that of children in the Nordinet ® study [20] , the girls with IGHD in the Australian OZGROW ® study [13] were younger, but not shorter ( Table 4 ).…”
Section: Discussionmentioning
confidence: 72%
“…Despite such discrepancies, it is worth remarking that GH levels were very similar among the individual diagnostic groups and across the 3 regions ( Table 2 ). While the height pattern in prepubertal males and females in this study was comparable to that of children in the Nordinet ® study [20] , the girls with IGHD in the Australian OZGROW ® study [13] were younger, but not shorter ( Table 4 ).…”
Section: Discussionmentioning
confidence: 72%
“…>−2 SDS). Mean change in IGF-1 SDS remained within the reference range (±2 SDS) after 2 years at a mean dose of 38 μg/kg/day [20]. IGF-1 SDS data beyond the initial 24 months of rhGH treatment are unavailable for the present prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Other analyses have also shown differences in response to GH treatment across diagnostic groups [31, 32]. For example, Lee et al [31] showed that change in height SDS was greater in children born SGA and smaller in those with idiopathic short stature when compared with children with idiopathic GHD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, final height of girls with Turner syndrome is positively influenced by height at GH initiation, the GH dose and age at onset of puberty, and negatively influenced by age at treatment initiation [29, 30]. Other analyses have also shown differences in response to GH treatment across diagnostic groups [31, 32]. For example, Lee et al [31] showed that change in height SDS was greater in children born SGA and smaller in those with idiopathic short stature when compared with children with idiopathic GHD.…”
Section: Discussionmentioning
confidence: 99%